Molecular Basis for Certain Neuroprotective Effects of Thyroid Hormone - Davis, Paul; Lin, Hung-Yun; Davis, Faith B.; Luidens, Mary; Mousa, Shaker; Cao, James; Zhou, Min (Frontiers in Molecular Neuroscience, 2011)
The pathophysiology of brain damage that is common to ischemia-reperfusion inury and brain trauma includes disordered neuronal and glial cell energetics, intracellular acidosis, calcium toxicity, extracellular excitotoxic glutamate accumulation and dysfunction of the cytoskeleton and endoplasmic reticulum. Thyroid hormone isoforms, 3, 5, 3'-triiodo-L-thyronine (T3) and L-thyroxine (T4), have nongenomic and genomic actions that are relevant to repair of certain features of the pathophysiology of brain damage. Thyroid hormone can nongenomically repair intracullar H+ accumulation by stimulation of the Na+/H+ exchanger and can support desirably low [Ca2+]i.c. by activation of plasma membrane Ca2+-ATPase. Thyroid hormone nongenomically stimulates astrocyte glutamate uptake, an action that protects both glial cells and neurons. The hormone supports the integrity of the cytoskeleton by its effect on actin. Several proteins linked to thyroid hormone action are also neuroprotective. For example, the hormone stimulates expression of the seladin-1 gene whose gene product is anti-apoptotic and is potentially protection in the setting of neurodegeneration. Transthyretin (TTR) is a serum transport protein for T4 that is important to blood-brain barrier transfer of the hormone and TTR has also been found to be neuroprotective in the setting of ischemia. Finally, the interesting thyronamine derivatives of T4 have been shown to protect against ischemic brain damage through their ability to induce hypothermia in the intact organism. Thus, thyroid hromone or hormone derivatives have experimental promise as neuroprotective agents.